Acupuncture for Treatment of Autism Spectrum Disorders. (6th December 2011) - Ming, Xue; Chen, Xiang; Wang, Xiao T.; Zhang, Zhen; Kang, Victor; Zimmerman-Bier, Barbie
Abstract : Background . There has been lack of reviews of evidence on efficacy, methodology, and/or safety of acupuncture in autism spectrum disorders. This paper examines the emerging evidence of the effects of acupuncture in the treatment of autistic children. Method . A literature review was completed via Medline and three Chinese search engines. A total of 31 studies were evaluated for acupuncture methodology, study design, treatment effects, and tolerability. Results . The acupoints used, the duration of needling, the frequency of treatment, the choice of stimulation, and the course of the treatment were highly variable amongst the studies. Behavioral and/or developmental improvements were reported in all acupuncture treatment studies. All studies reported general tolerability. Weakness of experimental designs was discussed. Conclusions . Vigorously controlled double-blinded clinical trials are needed to evaluate the efficacy and safety of acupuncture in children with autism spectrum disorders.